MEDIA, TERRORISM REPORTING AND LESSONS IN AWARENESS SUSTENANCE: the Nigerian newspapers’ coverage of the Chibok girls’ abduction - Ajakaiye, Olanrewaju O. P; Nwozor, Agaptus; Ojeka, John Dean; Aleyomi, Michael B.; Owoeye, Gbenga; Ojeka-John, Rachael; Okidu, Onjefu (Brazilian journalism research, 2021)
ABSTRACT – This study investigated how Nigerian newspapers contributed to sensitizing and sustaining public attention on the issue of the schoolgirls that were abducted by the Boko Haram group in Chibok, northeastern Nigeria. The study analyzed the direction/slant, frequency, and prominence of news stories, feature articles, editorials, special reports, interpretative articles, and news analysis on the abduction as published in three major Nigerian newspapers. Using the content analytical technique, the study found that there was no day in the period under investigation that the issue of the abducted Chibok girls did not get attention in the press. The study also found that the press discharged its corporate social responsibility by setting and sustaining public consciousness on the injustice and inhumanity of the abduction. Furthermore, a connection was established between the unrelenting crusade mounted by non-governmental organizations, especially the #BringBackOurGirls movement, for the release of the abducted girls, sustained public interest provided by the Press, and the eventual government action that culminated in the release of 164 out of the 276 girls initially abducted. This study, therefore, recommends continued publicity by the media in its role as a social crusader to ensure that the remaining Chibok and other abductees are rescued from their Boko Haram abductors. RESUMO – Este estudo investigou como os jornais nigerianos contribuíram para sensibilizar e manter a atenção do público sobre a questão das estudantes que foram sequestradas pelo grupo Boko Haram em Chibok, no nordeste da Nigéria. O estudo analisou o direcionamento/ponto de vista, a frequência e proeminência das notícias, artigos de destaque, editoriais, reportagens especiais, artigos interpretativos e análises de notícias sobre o sequestro nas publicações dos três principais jornais nigerianos. Usando técnica analítica de conteúdo, o estudo identificou que, no período investigado, não houve um dia em que a pauta do sequestro não tenha recebido atenção da imprensa. O estudo descobriu também que a imprensa cumpriu sua responsabilidade social corporativa ao estabelecer e manter a consciência pública sobre a injustiça e desumanidade do sequestro. Além disso, uma conexão foi estabelecida entre a cruzada incessante montada por organizações não governamentais, especialmente o movimento #BringBackOurGirls, pela libertação das meninas, e sustentou o interesse público proporcionado pela imprensa e a eventual ação governamental que culminou com a libertação de 164 das 276 garotas inicialmente sequestradas. Portanto, este estudo recomenda a continuidade da visibilidade proporcionada pela mídia no seu papel de cruzada social para assegurar que Chiboks e outros raptados sejam resgatados dos seus sequestradores do Boko Haram. RESUMEN – En este estudio se investiga cómo los periódicos nigerianos contribuyeron a sensibilizar y mantener la atención pública sobre la cuestión de las niñas secuestradas por el grupo Boko Haram en Chibok, al noreste de Nigeria. El estudio analizó la dirección/orientación, frecuencia y prominencia de las noticias, artículos de fondo, editoriales, informes especiales, artículos interpretativos y análisis periodísticos sobre el secuestro, publicados en tres importantes periódicos nigerianos. Mediante el uso de la técnica del análisis de contenido, el estudio llegó a la conclusión de que no había ningún día en el período investigado en que el asunto de las niñas Chibok secuestradas no recibiera atención en la prensa. También se encontró que la prensa cumplió con su responsabilidad social corporativa al establecer y mantener la conciencia pública sobre la injusticia y la falta de humanidad del secuestro. Además, se estableció una conexión entre la implacable cruzada montada por organizaciones no gubernamentales, especialmente el movimiento #BringBackOurGirls, por la liberación de las niñas secuestradas, el interés público sostenido proporcionado por la prensa, y la eventual acción gubernamental que culminó en la liberación de 164 de las 276 niñas inicialmente secuestradas. Por lo tanto, en este estudio se recomienda que los medios de comunicación continúen otorgando publicidad, en su rol público de luchadores sociales, para garantizar que los restantes Chibok y otros secuestrados sean rescatados de sus secuestradores de Boko Haram.